Synthesis of Silver Nanoparticles by Green Method Using Green Tea Leaves Extract, Morphology, Optical, and Antibacterial Properties of Silver Nanoparticles - Yu, Soon Wing; Haider Rizvi, Syed Zuhaib (Enhanced Knowledge in Sciences and Technology, 2024)
Silver nanoparticles (AgNPs) is well-known to have antibacterial properties , while biosynthesis method is an environmentally friendly to produced AgNPs.Conventional method often face challenges in safety concerns and nanoparticle aggregation. Therefore, this research was performed to determine the method of synthesizing AgNPs by green tea extract, investigate its morphology, element analysis, optical and antibacterial activity. The AgNPs were produced by mixing 0.01mol/L of silver nitrate solution with green tea extract to get the liquid sample, centrifuged and dried for powder sample. Antibacterial activity of AgNPs is tested against Escherichia coli (E.coli), while morphology, element analysis, and optical properties are determined by using scanning electron microscopy (SEM), energy-dispersive X-ray (EDX), and ultraviolet-visible spectroscopy (UV-Vis). The results show blue shift for the graph of UV-Vis, EDX shows 64.19% of Ag presents, zone of inhibition of AgNPs is around 7 to 13 mm, and no nano particles exist as refer to SEM images.